Jovens cegos tateando os seus projetos de vida: um estudo sobre suas representações - Nascimento, Ivany Pinto; Nascimento, Lourival (Revista Cocar, 2020)
Young blind feeling your life projects: a study on their representations Resumo O artigo apresenta os resultados parciais do estudo desenvolvido no período de 2017 a 2018, com os seguintes questionamentos: como os jovens com cegueira que moram na Amazônia paraense, compartilham conhecimentos sobre seus Projetos de Vida e qual a importância que atribuem à escola para a realização desses projetos? O instrumento utilizado foi a entrevista com roteiro preestabelecido. Os sujeitos entrevistados foram 10 jovens cegos estudantes, na faixa etária entre 15 a 29 anos, vinculados a Unidade Técnica Educacional Especializada José Álvares de Azevedo. A Análise de Conteúdo de Bardin (1997) foi utilizada para identificar o pensamento consensual de jovens cegos sobre seus projetos de vida. Os resultados parciais apontam o seguinte: que as representações sociais sobre o projeto de vida transitam entre a educação e o trabalho e que a escola, necessita de mudanças. Palavras-chave: Juventude; Diversidade; Representações. Abstract The article aims to present the partial results of the study conducted from 2017 to 2018, with the following questions: how young people with blindness who live in the Paraense Amazon, northern region of the country, share knowledge about their Life Projects and how important is it assign to the school to carry out these projects? It deals with a research of procedural approach, the theoretical and methodological field of Social Representations. The instrument used was the interview with pre-established script in the form of themes about the life project. The subjects interviewed were 10 young blind students, equally distributed among young women and young men aged 15 to 29 years, linked to José Álvares de Azevedo Specialized Educational Technical Unit (UTES JAA). Bardin's Content Analysis (1997) was used to identify the consensus thinking of blind young people about their life projects. The partial results point to the following: that social representations reflect the images and meanings about the life project that transit between Education, Work; that the school, without reframing the rationality with which the teaching learning process materializes, now represents an obstacle to both school inclusion and the achievement of its life projects. Keywords: Youth; Diversity; Representations.